A Pilot Study on Across-Generation Impacts of Maternal Heat Stress on Blood Metabolites of Female Holstein Dairy Calves - Halli, Kathrin; Cohrs, Imke; Brügemann, Kerstin; Koch, Christian; König, Sven; Justus Liebig University Giessen (My University, 2023)
Heat stress (HS) during late gestation implies unfavorable effects on dairy cows and their in-utero heat stressed offspring. The objective of the present study was to elucidate the effect of intrauterine (maternal) HS during the last week of gestation on blood metabolite concentrations of female dairy calves during their first week of life. We defined the mean temperature humidity index (mTHI) during the last gestation week of ≥60 as threshold for maternal HS. In this regard, we compared differences in metabolite concentrations of maternally heat stressed (MHSCALVES) (n = 14) and not heat stressed (NMHSCALVES) (n = 33) calves. We identified 15 metabolites from five different biochemical classes (phosphatidylcholines, cholesteryl esters, sphingomyelins, cresols and hexoses) as potential biomarkers for maternal HS in calves. The plasma concentrations of all significantly affected metabolites were lower in MHSCALVES when compared to NMHSCALVES. The effect of maternal HS during the last week of gestation on blood metabolite concentrations of the female offspring during the first week after birth might be due to HS induced intergenerational physiological alterations, impaired colostrum quality or epigenetic modifications of the calf genome. The results of this pilot study should be validated in ongoing fully standardized studies.
Keywords: dairy calves; maternal heat stress; plasma metabolome; ddc:630